2007
DOI: 10.1073/pnas.0610485104
|View full text |Cite
|
Sign up to set email alerts
|

PfEMP1-DBL1α amino acid motifs in severe disease states of Plasmodium falciparum malaria

Abstract: An infection with Plasmodium falciparum may lead to severe malaria as a result of excessive binding of infected erythrocytes in the microvasculature. Vascular adhesion is mediated by P. falciparum erythrocyte membrane protein-1 (PfEMP1), which is encoded for by highly polymorphic members of the var-gene family. Here, we profile var gene transcription in fresh P. falciparum trophozoites from Ugandan children with malaria through var-specific DBL1␣-PCR amplification and sequencing. A method for subsectioning reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 39 publications
7
113
0
1
Order By: Relevance
“…The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51). Previously, the only known binding phenotype for group A PfEMP1 variants was rosetting (20)(21)(22)(23), with two group A domain cassettes (DC11 and DC16) being linked to rosette formation (24).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies addressing the relationship between var genes and clinical disease have found an association between group A var gene transcription and severe malaria or CM (16)(17)(18)(19)51). Previously, the only known binding phenotype for group A PfEMP1 variants was rosetting (20)(21)(22)(23), with two group A domain cassettes (DC11 and DC16) being linked to rosette formation (24).…”
Section: Discussionmentioning
confidence: 99%
“…As children grow and expand their antibody repertoire (83-85), they become susceptible to fewer and fewer P. falciparum strains. Genome and expression analyses have shown that the PfEMP-1 family has a vast capacity for sequence diversification (86,87), and some PfEMP-1 variants may cause more severe clinical outcomes than others (88,89). Structural constraints on the extracellularbinding domains of PfEMP-1 may restrain the ability of different variants to escape recognition by cross-reactive antibodies, thus allowing some degree of protection between strains (90,91).…”
Section: Figurementioning
confidence: 99%
“…3 Both host and parasite determinants were attributed to severe malarial disease. [4][5][6] Several studies have shown the involvement of proinflammatory cytokines in pathogenesis of severe falciparum malaria where high plasma TNF-alpha, IL-1beta, IL-6, IL-10, and IFN-gamma levels were associated with severe disease. [7][8][9][10] Cerebral malaria patients were shown to have high TNF-alpha levels, 7 whereas severely anemic children had low TNF-alpha levels comparable to that of mild malaria.…”
Section: Introductionmentioning
confidence: 99%